2021
DOI: 10.1109/emr.2021.3052928
|View full text |Cite
|
Sign up to set email alerts
|

Teleconsultation Apps in the COVID-19 Pandemic: The Case of Guayaquil City, Ecuador

Abstract: The new coronavirus disease (COVID-19) has affected a large part of the worldwide population, causing more than a million deaths between the end of 2019 until now. Technological development and digital tools arise to carry out activities remotely, either for monitoring or diagnosis. Medical teleconsultation activities are not new, but due to the pandemic situation that the COVID-19 originated, it has become a popular option to avoid going to consultations physically due to the risk of contagion. This article p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 32 publications
0
22
0
Order By: Relevance
“…Perez-Noboa et al ( 35 ) reported on telemedicine for continuous vital sign monitoring, which used telemedicine in conjunction with body sensors to provide healthcare providers with continuous updates on the patient's health status. Caetano et al ( 6 ) identified telemedicine as a component of “online/virtual hospitals,” stating that “virtual clinics can be assembled using telemedicine consultations, including imaging tests (e.g., chest x-ray and/or chest computerized tomography—CT, relevant for assessing pulmonary involvement from the coronavirus), uploaded from peripheral sites and interpreted remotely,” ensuring that patients received clinical care while also minimizing physical crowding in hospital facilities.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Perez-Noboa et al ( 35 ) reported on telemedicine for continuous vital sign monitoring, which used telemedicine in conjunction with body sensors to provide healthcare providers with continuous updates on the patient's health status. Caetano et al ( 6 ) identified telemedicine as a component of “online/virtual hospitals,” stating that “virtual clinics can be assembled using telemedicine consultations, including imaging tests (e.g., chest x-ray and/or chest computerized tomography—CT, relevant for assessing pulmonary involvement from the coronavirus), uploaded from peripheral sites and interpreted remotely,” ensuring that patients received clinical care while also minimizing physical crowding in hospital facilities.…”
Section: Resultsmentioning
confidence: 99%
“…Over half of included studies ( n = 31, 57.4%) discussed the need of telemedicine in resuming the provision of healthcare services that had been halted owing to lockdown measures, movement restrictions, and social distancing policies. Several articles ( n = 16, 29.6%) recognized telemedicine as a promising option to compensate for doctors' limited availability ( 6 , 7 , 31 , 35 47 ). Also, several others ( n = 13, 24.0%) identified telemedicine as a preventive method for reducing physical interactions and hence lowering the risk of patients contracting COVID-19 ( 48 50 ) Some studies ( n = 9, 16.7%) reported lowering the risk for healthcare workers ( 6 , 24 , 26 , 35 , 44 , 48 , 50 , 51 ), others ( n = 4, 7.4%) emphasized telemedicine's need to address disparities in healthcare worker distribution and high healthcare costs ( 40 , 42 , 47 , 51 , 52 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Teleconsultation themes in literature focus on performance improvement of the proposed solutions ( Pérez-Noboa et al, 2021 ) and analyze adoption factors by using technology acceptance models ( Baudier et al, 2021 ; Rahi et al, 2020 ; Dash et al, 2021 ; Barua and Barua, 2021 ). The intersection of both medical and technology research paths contributes to the understanding of the challenges and insights of teleconsultation.…”
Section: Theoretical Backgroundmentioning
confidence: 99%